EVALUASI DIMENSI SETTLING POND 6 BLOK KEUNO PADA PT. BUKIT MAKMUR INSTINDO NIKELTAMA (BUMANIK) KECAMATAN PETASIA TIMUR KABUPATEN MOROWALI UTARA PROVINSI SULAWESI TENGAH - Supriandi; Gina Audina P Alhabsyi; Ruth Bunga R (Journal Teknik Dan Teknologi, 2025)
The purpose of this study was to determine the dominance size of the settling pond, calculate the discharge and the runoff volume of the Keuno Block B Pit. The purpose of making this settling pond is to accommodate runoff water flow that will enter the mining area in Pit B of the Keuno Block. The research method used is descriptive research to provide information about facts and phenomena that occur at the research site. Data was collected through field observations, interviews, and document studies. Association obtained 1) Water entering the Pit B Block of Keuno in the form of runoff water with a discharge of 2,72 m3 / sec at DTH, 0,609 m3 / sec at DTH II, and 1,081 m3 / sec at DTH III 1,069 m3 / sec. 2) From the results of runoff discharge calculations, the dimensions of the first settling pond plan are made: Water Discharge (Q) = 2,72 m3 / sec, Pool Volume (V) = 1000 m3, Pool Length I ( P) = 35 m, Pool Length II (P) 30 m, Pool length III (P) 25 m. Pool side width I (L) = 24 m, Pool side width II (L) 22 m, Pool side width (L) = 20 m. Pool Depth (d) = 5 m.